Pre-operative anaemia is associated with total morbidity burden on days 3 and 5 after cardiac surgery: a cohort study. Issue 1 (December 2017) - Sanders, Julie; Cooper, Jackie; Farrar, Daniel; Braithwaite, Simon; Sandhu, Updeshbir; Mythen, Michael; Montgomery, Hugh
Abstract Background Pre-operative anaemia is associated with mortality and red blood cell (RBC) transfusion requirement after cardiac surgery. However, the effect on post-operative total morbidity burden (TMB) is unknown. We explored the effect of pre-operative anaemia on post-operative TMB. Methods Data were drawn from the Cardiac Post-Operative Morbidity Score (C-POMS) development study (n  = 442). C-POMS describes and quantifies (0–13) TMB after cardiac surgery by noting the presence/absence of 13 morbidity domains on days 3 (D3), 5 (D5), 8 (D8) and 15 (D15). Anaemia was defined as a haemoglobin concentration below 130 g/l for men and 120 g/l for women. Results Most patients were White British (86.1%) and male (79.2%) and underwent coronary artery bypass surgery (67.4%). Participants with pre-operative anaemia (n  = 137, 31.5%) were over three times more likely to receive RBC transfusion (OR 3.08, 95%CI 1.88–5.06, p  < 0.001), had greater D3 and D5 TMB (5 vs 3, p  < 0.0001; 3 vs 2, p  < 0.0001, respectively) and remained in hospital 2 days longer (8 vs 6 days, p  < 0.0001) than non-anaemic patients. Transfused patients remained in hospital 5 days longer than non-transfused patients (p  < 0.0001), had higher TMB on all days (allp  < 0.001) and suffered greater pulmonary, renal, GI, neurological, endocrine and ambulation morbidities (p 0.026 to <0.001). Pre-operative anaemia and RBC transfusion were independently associated with increased C-POMS score. Conclusions Pre-operative anaemia and RBC transfusion are independently associated with increased post-operative TMB. Understanding TMB may assist in post-operative patient management to reduce morbidity. We recommend the use of the C-POMS tool as a standard outcome tool in further studies.